Adapting the WHO Behavioural and Social Drivers of Vaccination (BeSD) tools and Vaccination Attitudes Examination (VAX) scale for pregnant women in South Africa: Insights from a mixed-methods pilot study - Imen Ayouni; Jennifer Nyawira Githaiga; Edina Amponsah-Dacosta; Benjamin M. Kagina; Rudzani Muloiwa (PLoS ONE, 2025)
Background Understanding vaccine attitudes, knowledge, and perceptions is critical for improving vaccine uptake, particularly among vulnerable populations such as pregnant women. This study aimed to test and adapt quantitative survey tools and an interview guide for assessing maternal and childhood vaccine attitudes among pregnant women in the South African context. Methods We conducted a mixed-methods pilot study among pregnant women attending antenatal care at two public hospitals in Cape Town, South Africa, between September 2023 and January 2024. Quantitative data were collected using a self-administered questionnaire on tablets, incorporating the adapted BeSD and VAX tools, while qualitative data were gathered through semi-structured interviews. Additionally, the quantitative questionnaire contained the General Vaccine Attitude Survey questions developed by the World Health Organization Strategic Advisory Group of Experts on Immunization (WHO SAGE) Working Group on Vaccine Hesitancy and a validated tool on knowledge of influenza and attitudes toward influenza vaccination during pregnancy. Adaptations to the tools were informed by participant feedback and pretesting. Results Eighty pregnant women agreed to participate in the quantitative survey, one participant dropped out of the study and seven completed follow-up qualitative interviews. The tools were well received, with participants reporting ease of use and understanding. Minor linguistic adjustments improved clarity, and participants identified healthcare providers as key influencers in vaccine decision-making. Knowledge gaps regarding maternal vaccination and concerns about vaccine safety during pregnancy were prominent. The mixed-methods approach provided complementary insights into the tools’ applicability and participants’ attitudes. Conclusions This pilot study demonstrated that the WHO BeSD tools, the VAX Scale, the General Vaccine Attitude Survey, and the questions on knowledge of influenza and attitudes toward influenza vaccination during pregnancy, with minor adaptations, are feasible and acceptable for use in South Africa. These findings support their application in larger studies to explore maternal vaccine confidence and decision-making. Addressing knowledge gaps and leveraging trusted sources of information is critical to enhancing vaccine uptake in similar settings.